Negative comparisons about one's appearance mediate the relationship between Facebook usage and body image concerns. (January 2015) - Fardouly, Jasmine; Vartanian, Lenny R.
Highlights: Facebook usage was associated with body image concerns (BIC) in young women. Facebook appearance comparisons mediated the Facebook usage–BIC relation. Comparison frequency to peers on Facebook mediated the usage–BIC relation. Comparison direction to peers and celebrities mediated the usage–BIC relation. Abstract: Use of social media, such as Facebook, is pervasive among young women. Body dissatisfaction is also highly prevalent in this demographic. The present study examined the relationship between Facebook usage and body image concerns among female university students ( N  = 227), and tested whether appearance comparisons on Facebook in general, or comparisons to specific female target groups (family members, close friends, distant peers [women one may know but do not regularly socialize with], celebrities) mediated this relationship. Results showed a positive relationship between Facebook usage and body image concerns, which was mediated by appearance comparisons in general, frequency of comparisons to close friends and distant peers, and by upward comparisons (judging one's own appearance to be worse) to distant peers and celebrities. Thus, young women who spend more time on Facebook may feel more concerned about their body because they compare their appearance to others (especially to peers) on Facebook.